2020
DOI: 10.1177/0036850420936220
|View full text |Cite
|
Sign up to set email alerts
|

A novel model for low-cycle multiaxial fatigue life prediction based on the critical plane-damage parameter

Abstract: Multiaxial fatigue of the components is a very complex behavior. This analyzes the multiaxial fatigue failure mechanism, reviews and compares the advantages and disadvantages of the classic model. The fatigue failure mechanism and fatigue life under multiaxial loading are derived through theoretical analysis and formulas, and finally verified with the results of multiaxial fatigue tests. The model of multiaxial fatigue life for low-cycle fatigue life prediction model not only improves the prediction accuracy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Fatigue life prediction has an important impact on the design, use and maintenance of parts. [41][42][43][44] It is the key to ensuring safety. Before the life estimation of the lower arm, the fatigue life corresponding to the onedimensional load spectrum needs to be found first.…”
Section: Fatigue Life Prediction Of Lower Armmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatigue life prediction has an important impact on the design, use and maintenance of parts. [41][42][43][44] It is the key to ensuring safety. Before the life estimation of the lower arm, the fatigue life corresponding to the onedimensional load spectrum needs to be found first.…”
Section: Fatigue Life Prediction Of Lower Armmentioning
confidence: 99%
“…Fatigue life prediction has an important impact on the design, use and maintenance of parts 41–44 . It is the key to ensuring safety.…”
Section: Fatigue Life Prediction Of Lower Armmentioning
confidence: 99%
“…Currently, most multiaxial fatigue life prediction models can accurately predict fatigue life under proportional loading (Brown and Miller, 1973;Sun et al, 2022;Branco et al, 2022;Nourian-Avval and Khonsari, 2021;Guechichi et al, 2011), while the prediction results for fatigue life under non-proportional loading conditions are often not accurate enough (Ma and Liu, 2022). This is due to the constant rotation of the principal strain axis under non-proportional loading conditions, and the material does not easily produce a stable dislocation structure internally, leading to non-proportional additional hardening phenomena (Liu et al, 2020). Liu et al (2022) found that the larger the phase difference, the more obvious the additional hardening effect, and the most serious additional hardening phenomenon was observed when the phase difference was 908.…”
Section: Introductionmentioning
confidence: 99%
“…, 2011), while the prediction results for fatigue life under non-proportional loading conditions are often not accurate enough (Ma and Liu, 2022). This is due to the constant rotation of the principal strain axis under non-proportional loading conditions, and the material does not easily produce a stable dislocation structure internally, leading to non-proportional additional hardening phenomena (Liu et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing that a fatigue criterion cannot accurately estimate fatigue life by only considering the stress/strain state inside a material in terms of the computation of a suitable damage parameter. Among the criteria available in the literature for such an evaluation, both strain-and energy-based criteria are widely used [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%